Contemporary issues in ensuring biological safety during disposal of biological wastes of animal origin by incineration in the Russian Federation - A. V. Belchikhina; M. A. Shibayev; A. M. Selyanin; A. K. Karaulov (Ветеринария сегодня)
Animal management and breeding as well production, transportation, preparation, and processing of animal products and raw material result in generation of a considerable amount of biological wastes being a source of biological contamination of the environment and a clear threat to human and animal health. The animal biowaste incineration units are high threat facilities and require constant surveillance and control. Collection and analysis of data provided by the RF veterinary executive authorities were performed to objectively reflect the actual situation of the biological waste incineration facilities in the RF Subjects and to create a holistic view on the problem of interest in the country. The following parameters were analyzed: their number, type (stationary and mobile), type of ownership, location, availability of the certificate and highly-qualified specialists serving the biological waste incineration equipment as well as the availability of such facilities in the RF Subjects as for January 1, 2021. The analysis demonstrated that 4,459 biowaste incinerators were registered in the country. Most of these units are stationary and they belong to establishments involved in farm animal keeping, animal product processing, production and storing. Such equipment is mostly serviced by non-qualified staff ignorant of the technical characteristics and operating principles of this equipment. Almost one third of these units in the country are home made that is why their use does not guarantee complete destruction of biological wastes and pathogen inactivation. It was also revealed that the procedure for the incineration of biological waste of animal origin using home made incinerators is not legally fixed in the country. The results obtained show that the situation of the animal biowaste incineration in the Russian Federation is quite complicated.